Microsporidia are natural intracellular parasites of the nematode Caenorhabditis elegans. - Emily R Troemel (Public Library of Science (PLoS), 2008)
For decades the soil nematode Caenorhabditis elegans has been an important model system for biology, but little is known about its natural ecology. Recently, C. elegans has become the focus of studies of innate immunity and several pathogens have been shown to cause lethal intestinal infections in C. elegans. However none of these pathogens has been shown to invade nematode intestinal cells, and no pathogen has been isolated from wild-caught C. elegans. Here we describe an intracellular pathogen isolated from wild-caught C. elegans that we show is a new species of microsporidia. Microsporidia comprise a large class of eukaryotic intracellular parasites that are medically and agriculturally important, but poorly understood. We show that microsporidian infection of the C. elegans intestine proceeds through distinct stages and is transmitted horizontally. Disruption of a conserved cytoskeletal structure in the intestine called the terminal web correlates with the release of microsporidian spores from infected cells, and appears to be part of a novel mechanism by which intracellular pathogens exit from infected cells. Unlike in bacterial intestinal infections, the p38 MAPK and insulin/insulin-like growth factor (IGF) signaling pathways do not appear to play substantial roles in resistance to microsporidian infection in C. elegans. We found microsporidia in multiple wild-caught isolates of Caenorhabditis nematodes from diverse geographic locations. These results indicate that microsporidia are common parasites of C. elegans in the wild. In addition, the interaction between C. elegans and its natural microsporidian parasites provides a system in which to dissect intracellular intestinal infection in vivo and insight into the diversity of pathogenic mechanisms used by intracellular microbes.